SDN in the home: A survey of home network solutions using Software Defined Networking - Abdalkrim M. Alshnta; Mohd Faizal Abdollah; Ahmed Al-Haiqi (Cogent Engineering, 2018)
Software Defined Networking (SDN) is an important paradigm shift of computer networking in the last 10 years. The concept of SDN is so powerful that the potential of applying it can easily be perceived beyond the initial use case of large data centre networks. We are motivated by this perception to explore the potential use of SDN in the context of home networks specifically, even though home environments were not the driving scenario behind SDN in the first years of its development. Lacking other reviews on the subject, we performed a focused search for every article that proposes, discusses or otherwise addresses the idea of implementing SDN in home networking. We surveyed four major technical and online databases (IEEE Xplore, ACM, ScienceDirect and Wiley) to ensure the inclusion of relevant, quality and authentic works. The final filtered set included 42 articles that spanned the period from 2010 to 2017. Most of the articles address specific aspects of controlling and managing home networks, such as Quality of Experience, security, Internet caps, Internet-of-Things device management and other specific themes, while the rest of articles address the generic case of managing home networks using SDN without a special focus on a particular target application. We derive a simple taxonomy for the works on home SDN and summarize the complete set of works, highlighting few points along the way and drawing few simple statistics.